2013
DOI: 10.1016/j.brachy.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-dose-rate brachytherapy for uterine cervix carcinoma: 10 years of experience with 226 patients at a single institution

Abstract: This study demonstrates excellent LC rates with few late side effects with PDR BT for cervix carcinoma, similar to those reported in the literature with historical standard low-dose-rate BT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…Seeger et al 69 included Gy after EBRT in all types of gynaecological tumours. LC of 53% was lower than that of the more recent studies, [10][11][12]65 with GI, GU and gynaecological Grade 3 toxicity approximately 15%.…”
Section: Sarcomas Of the Extremitiescontrasting
confidence: 63%
See 1 more Smart Citation
“…Seeger et al 69 included Gy after EBRT in all types of gynaecological tumours. LC of 53% was lower than that of the more recent studies, [10][11][12]65 with GI, GU and gynaecological Grade 3 toxicity approximately 15%.…”
Section: Sarcomas Of the Extremitiescontrasting
confidence: 63%
“…[9][10][11][12][13][14][15][16][17][18][19] Articles were published between 1997 and 2013 and mostly 9 reported data only for a subset of patients for whom optimization was performed on CT scan or MRI. In all studies, intracavitary PDR was performed with a tandem and ovoids, but occasionally a mould was used in the STIC-PDR study.…”
Section: Resultsmentioning
confidence: 99%
“…Brachytherapy, a commonly applied therapeutic modality in the treatment of gynaecological [1][2][3] and prostate cancer [4], is continuously gaining more acceptance as a method expanding the role of conventional percutaneous radiotherapy in the treatment of head and neck cancer [5,6]. Its range of application includes primary disease, recurrences and residual tumour.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of image‐guided adaptive brachytherapy (IGABT) over the last decade has resulted in a pjmirodigm shift in the treatment approach to cervix cancer from point‐based dosimetry to volume‐based dosimetry. This has resulted in significant improvements to local control and reduced toxicity, Table . Previous reports have demonstrated that centres in Australia are adopting image‐guided protocols with an increase in the use of 3D imaging in brachytherapy planning from 27% in 2005 to 65% in 2009 .…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in significant improvements to local control and reduced toxicity, Table 1. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Previous reports have demonstrated that centres in Australia are adopting image-guided protocols with an increase in the use of 3D imaging in brachytherapy planning from 27% in 2005 to 65% in 2009. 17,18 The purpose of this survey was to explore the current patterns of practice for brachytherapy in cervix cancer in Australia and New Zealand.…”
Section: Introductionmentioning
confidence: 99%